Sistem Pemasaran Dropship dalam Perspektif Islam - Cahyadi, Iwan Fahri (Sharia Faculty Islamic Economic Law Study Department, 2018)
Companies that want to survive must be able to adapt and respond to changes in the business environment, whether it's internal and external environment. Companies that are not able to adapt to changing environment then it will fail in his efforts. One of the changes that are happening at the moment is the marketing system with a system of dropship. On the other hand being debated dropship marketing system for the leaders of religion in Indonesia. There are some religious leaders denounce as there are elements of gharar and partly justifies. Islam is the perfect religion. Most of the religious leaders gave an answer that is clearly selling dropship allowed in Islam with a record must meet the Islamic jurisprudence. The solution is through the Covenant of samirah, wakalah and salam. Thus the law of selling dropship system is allowed, as long as there are no prohibited items.